Designs on Pots Ban Chiang and the Politics of Heritage in Thailand - Van Esterik, Penny (Asian Heritages, 2023)
The prehistoric site of Ban Chiang in northeast Thailand challenges the narrative of Thai origins, while at the same time appealing to the public's vision of Thailand as an early centre of civilization. Ban Chiang demonstrates the complexity of constructing national heritage in modern Thailand, where the Thai national narrative begins and ends with Buddhism and the monarchy. Designs on Pots. Ban Chiang and the Politics of Heritage in Thailand contributes to the literature on cultural preservation, repatriation, fake antiquities as souvenirs, and the ethics of collecting and demonstrates how heritage tourism intersects with the antiquities market in Asia. Ban Chiang itself is important for rethinking the model of indigenous development in Southeast Asian prehistory and provides informed speculation about the borders between prehistory, proto-history, and history in the region, challenging current and past models of Indianization that shape the Thai state's heritage narrative.